THE REALIZATION OF ADVICE IN DA'WAH PROGRAM(A DESCRIPTIVE ANALYSIS OF ADVICE REALIZATION USED BY DA'I IN CERMIN HATI PROGRAM) - Fitri Juniarsih, - (2009)
The paper entitled "The Realization of Advice in Da'wah Program (A Descriptive Analysis of Advice Realization by Da'is in Cermin Hati Program)" aims to investigate two aspects. The first is the advice strategies which are used by Indonesian da'is. The second is the relationship between the style of the da'is and the realization of advice. Data was collected through a 30 minutes of audio-recording of an Islamic Program, namely Cermin Hati on Global TV. The data were recorded twice in order to obtain the utterances of two da'is, those are Jefri Al-Buchori and Ahmad Al-Habsyi. All of the utterances were transcribed and analyzed by classifying advice expressions into advice strategies which are proposed by Flor (2005). The findings show that Jefri Al-Buchori used mostly indirect-hints advice. On the other hand, Ahmad Al-Habsyi frequently used direct-imperative advice. Additionally, there are four aspects that indicate the style of the da'is in terms of formality, i.e. reference terms, lexical choice, phonological forms, and morphological forms. Based on the findings, Jefri Al-Buchori's style is more informal than Ahmad Al-Habsyi. Thus, it can be concluded that formality seems to lead to imperative strategies, and informality lead to hints strategies.